Ginseng administration protects skeletal muscle from oxidative stress induced by acute exercise in rats - Voces,J. (2004)
Enzymatic activity was analyzed in the soleus, gastrocnemius (red and white) and plantaris muscles of acutely exercised rats after long-term administration of Panax ginseng extract in order to evaluate the protective role of ginseng against skeletal muscle oxidation. Ginseng extract (3, 10, 100, or 500 mg/kg) was administered orally for three months to male Wistar rats weighing 200 ± 50 g before exercise and to non-exercised rats (N = 8/group). The results showed a membrane stabilizing capacity of the extract since mitochondrial function measured on the basis of citrate synthase and 3-hydroxyacyl-CoA dehydrogenase activities was reduced, on average, by 20% (P < 0.05) after exercise but the activities remained unchanged in animals treated with a ginseng dose of 100 mg/kg. Glutathione status did not show significant changes after exercise or treatment. Lipid peroxidation, measured on the basis of malondialdehyde levels, was significantly higher in all muscles after exercise, and again was reduced by about 74% (P < 0.05) by the use of ginseng extract. The administration of ginseng extract was able to protect muscle from exercise-induced oxidative stress irrespective of fiber type.